Estimate of the Concentrations of Heavy Metals in Soil and Some Plant Samples Collected from (Near and Far away) of the Main Road between Al-Bayda City and Wadi Al-Kouf Region - Najat Al-Nayyan; Basit Mohammed; Hamad Hasan (AlQalam Journal of Medical and Applied Sciences, 2025)
This study was conducted on soli and the leafs and stem samples of Artemisia and Junipers plants collected from three areas located at west of the Al-Bayda city included (Farshita - Sidi Abdel Wahid - Wadi Al-Kouf regions) on the main road between Al-Bayda City and Wadi Al-Kouf region for estimate some of heavy metals in soil and some plants, as juniper and terabits plants samples collected during the fall and winter seasons. This study included five heavy metals: lead, cadmium, iron, chromium, and manganese. The results showed that the heavy metals detected in plants had different contents, where the highest concentration was recorded in the soil samples during the two seasons compared with their contents in leaves and stems. The concentration of cadmium showed lower concentrations in the leaves and stems in the third region, comparing to highest concentration of 19.669 ppm which observed in the stems in the area near the road, as well as chromium, recorded highest concentration of 231.014 ppm in the third region in the soil near the road, and its lowest concentration was 0.925 in the stems in the third region located far from the road, while for iron, the results showed highest concentration of 3516.9 ppm was the winter season for the soil sample of the area far from the road, and its lowest concentration was 67.665 ppm in the third region in the leaves of the Juniperus plant near the road. The highest concentration of lead was recorded in the first zone for the Juniperus plant, of 78,384 ppm near the road during the autumn, and the lowest concentration was recorded in the leaves in the third zone away from the road. The concentration of manganese in the first zone near the road in the soil was up to 2126 ppm in the winter in the Artemisia plant, and the lowest concentration was up to 9.862 ppm in the juniper plant in the third zone near the road in the stems.